O espelho e a duplicacao do eu - Souza, Ivete Vidigoi de (2005)
The purpose of this work is to starting the miror metaphor show some characteristics that are related to the double of two literature characters The major characters which have permited the analysis of the unveilling ways of the double are in two short stories both entitled \"The mirror\"one of the written by machado de Assis 19th century brazilian author and the by Guimarães Rosa another brazilian writer of the 20 th century The study of this two short stories text structure is based on Bakthin\'s polyphonic principles While Piglia\'s theory has provide the elements for the analyses of the short story by Machado de Assis Guimarães Rosa\'s short story was analyzed from an essaystic sight based on Adorno´s teory This research aims at a new reading for a treme wich has been superficially theorised so far and wich, therefore should be enlightened by deeper studies